Weak decay of uniformly accelerated protons and related processes - Vanzella, Daniel A. T. [UNESP]; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2001)
We investigate the weak interaction emission of spin-1/2 fermions from accelerated currents. As particular applications, we analyze the decay of uniformly accelerated protons and neutrons, and the neutrino-antineutrino emission from uniformly accelerated electrons. The possible relevance of our results to astrophysics is also discussed.